GLOBALIZATION AS A PHENOMENON OF CROSS-CULTURAL AND IDEOLOGICAL BASIS FORMATION - Abuov Amrekul (Scientific Journal of Pedagogy and Economics, 2020)
The current era of globalization is a complex and multifaceted phenomenon. One of its most important aspects is "the gradual formation of a common human humanitarian: cultural, ideological, moral and ethical basis, which brings together nations and peoples with different civilizations, histories, traditions and cultures." In today's globalization, in particular, in the formation of its humanitarian foundations must use the cultural heritage of all civilizations, which will enrich each nation and the world community, but each nation will always preserve its language, religion and national values, distinguishing between cultures. Imitating the culture of another nation, which must remain, means inevitably kneeling. However, in recent times there has been a dominance of only one dominant power in world civilization. In other words, globalization of "Americanization", which relies on the financial and economic power of transnational corporations, is gaining momentum. Such a trend does not have a onesided effect in developing countries, as well as in Europe. Despite the fact that today the concept of globalization is widely known, D.V. Ivanov points out: “The first signs of a crisis in the global paradigm of change are obvious. By simulating economic integration, the formation of a transnational bureaucracy, and the growth of multicommunities, the theory of globalization does not describe similar new trends that emerged in the late twentieth century: the influence of simulations, as well as computer revolution and cyber. In general, the concept of globalization in sociology includes a wide range of events and trends: the development of world ideologies, the intensive struggle for world order; increasing the number and influence of international organizations, weakening the independence of nation-states; emergence and development of transnational corporations, growth of international trade; mass migration and creation of multi-communities; the creation of global media and the invasion of Western culture in all regions of the world, etc. Despite extensive research by sociologists in the field of the theory of globalization, modern foreign researchers show that economic and political concepts are widespread. These studies are often supplemented by an analysis of cultural opportunities, which is associated with the role of the state, the economy and the technological revolution. Many authors also point out that global competition has negative consequences, even in the Western labor market. For example, the German sociologist Erich Veda noted that the restriction of world free trade does not benefit not only Western countries, but also non-capitalist countries. First, poor countries that have lost Western markets are "forced to feel hatred of the West." Second, globalization allows the West to shift some of its workers to higher-paying jobs in order to meet external demand. Third, for Western consumers, globalization means lower prices for many imported goods” [1]. In some of the works of recent years [2], it is hoped that the increase in prosperity will have an indirect effect on democracy and a direct reduction in the threat of war and conflict.